A meta‐analytic investigation of the relationship between HRM bundles and firm performance - Subramony, Mahesh (Human Resource Management, 2009)
AbstractHuman resource management bundles consisting of multiple complementary practices are typically considered superior to individual best practices in influencing firm performance. This study investigates the relationship between three such bundles (empowerment, motivation, and skill‐enhancing) and business outcomes (retention, operating performance, financial performance, and overall performance ratings). A meta‐analysis of 239 effect sizes derived from 65 studies reveals that HRM bundles have significantly larger magnitudes of effects than their constituent individual practices, are positively related to business outcomes, and display effect sizes that are comparable to or larger than those of high‐performance work systems. These findings reaffirm the case for firm‐level investments in synergistic HRM combinations and highlight the importance of investing in complementary practices. © 2009 Wiley Periodicals, Inc.